2012
DOI: 10.2337/diaspect.25.1.26
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to Increase Access to Care and Quality of Care for Women With Gestational Diabetes

Abstract: In Brief Women with a history of gestational diabetes mellitus (GDM) and their offspring have a lifelong risk of developing type 2 diabetes. Appropriate diagnosis and documentation are needed to ensure that these women receive interventions to reduce that risk. This article describes efforts of the multistate GDM Collaborative program to better understand GDM prevalence data, identify gaps in data quality and documented care, and develop interventions to improve access and postpartum follow-up c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…We do not know if this is evidence that the phase 6 question continues to overestimate true GDM prevalence or if it reflects a true increase in GDM prevalence. However, a recent study of 100 women in Utah who reported GDM on the phase 6 questionnaire but had no indication of GDM on their child’s birth certificate reported that 42% of these women did not have a GDM diagnosis in their medical records ( 15 ). Therefore, given the current limitations of both the birth certificate and PRAMS, true GDM prevalence is likely between the estimates obtained from the 2 sources.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We do not know if this is evidence that the phase 6 question continues to overestimate true GDM prevalence or if it reflects a true increase in GDM prevalence. However, a recent study of 100 women in Utah who reported GDM on the phase 6 questionnaire but had no indication of GDM on their child’s birth certificate reported that 42% of these women did not have a GDM diagnosis in their medical records ( 15 ). Therefore, given the current limitations of both the birth certificate and PRAMS, true GDM prevalence is likely between the estimates obtained from the 2 sources.…”
Section: Discussionmentioning
confidence: 99%
“…CDC periodically updates its PRAMS questions to reflect evidence-based revisions, with each revised version constituting a new phase. In a validation study of the PRAMS phase 5 (2007–2008) GDM question across 5 states, 61.8% of 277 study participants who reported GDM on the questionnaire did not have a GDM diagnosis in their prenatal or hospital medical records ( 15 ). In an attempt to reduce misclassification of GDM diagnosis based on maternal self-report, PRAMS revised the GDM question for phase 6 ( 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Policies should also be aimed at improving access and accommodating lifestyle changes. Moreover, population‐level strategies should focus on the role of women's health in society and highlight the importance of postpregnancy screening and care, balancing the role of mother and self‐care, and screening for gender‐based violence and mental health issues 64,65 …”
Section: Interventionsmentioning
confidence: 99%